1997
DOI: 10.1016/s0304-4017(97)00043-5
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic resistance in nematode parasites from goats in Spain

Abstract: In a flock of cashmere goats sited in Asturias (NW, Spain) diminished efficacy was observed following treatment with netobimin and consequently a study to demonstrate the existence of anthelmintic resistance and the species of nematode involved was conducted. Results from faecal egg count reduction tests before and after treatment with netobimin or ivermectin showed efficacies of 89.4 (81.8-94.8) and 99.7% (93.9-99.9%), respectively. Teladorsagia circumcincta was found to be the dominant species involved in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 16 publications
0
10
0
2
Order By: Relevance
“…In Spain, the first anthelmintic resistance recorded occurred after Cashmere goats were imported from the United Kingdom [78], where a high prevalence of anthelmintic resistance in fibre producing goats had been recorded [56]. The same situation was observed in Angora goats imported to Slovakia from New Zealand [96] and sheep imported to Greece from Great Britain [51].…”
Section: Introduction Of Animals Harbouring Anthelmintic Resistant Nementioning
confidence: 83%
“…In Spain, the first anthelmintic resistance recorded occurred after Cashmere goats were imported from the United Kingdom [78], where a high prevalence of anthelmintic resistance in fibre producing goats had been recorded [56]. The same situation was observed in Angora goats imported to Slovakia from New Zealand [96] and sheep imported to Greece from Great Britain [51].…”
Section: Introduction Of Animals Harbouring Anthelmintic Resistant Nementioning
confidence: 83%
“…Resistance is very low in Greece: on the mainland, there were only three cases of benzimidazole resistance out of 310 (1%) flocks, and animals had recently been introduced to the flocks; benzimidazole-resistant Teladorsagia circumcincta were found in 17 out of 106 flocks (10%) on small islands (Papadopoulos et al 2001). In Spain, after the first report of resistance in GI strongyles of Cashmere goats in 1997 (Requejo-Fernandez et al 1997), recently, Alvarez-Sanchez et al (2006 found that 12.7% of sheep flocks showed resistance to benzimidazoles. The figures in northern Africa, i.e.…”
Section: Introductionmentioning
confidence: 96%
“…The first report of AR was detected against netobimin in a flock of cashmere goats in Asturias (Northern Spain) (Requejo-Fernández et al 1997). Teladorsagia circumcinta was found to be the dominant species involved in netobimin resistance.…”
Section: Introductionmentioning
confidence: 98%